Fusarium chaquense, sp. nov, a novel type A trichothecene–producing species from native grasses in a wetland ecosystem in Argentina. (2nd January 2022) - Nichea, María J.; Proctor, Robert H.; Probyn, Crystal E.; Palacios, Sofía A.; Cendoya, Eugenia; Sulyok, Michael; Chulze, Sofía N.; Torres, Adriana M.; Ramirez, María L.
ABSTRACT: The Chaco wetland is among the most biologically diverse regions in Argentina. In collections of fungi from asymptomatic native grasses (Poaceae) from the wetlands, we identified isolates of Fusarium that were morphologically similar to F. armeniacum, but distinct from it by their production of abundant microconidia. All the isolates had identical, or nearly identical, partial sequences of TEF1 and RPB2 . But they were distinct from reference sequences from F. armeniacum and Fusarium species closely related to it. Phylogenetic analysis of 34 full-length housekeeping gene sequences retrieved from whole genome sequences of three Chaco wetland isolates, 29 genes resolved the isolates as an exclusive clade within the F. sambucinum species complex. Based on results of the morphological and phylogenetic analysis, we concluded that the Chaco wetland isolates are a distinct and novel species, herein described as Fusarium chaquense, sp. nov., which is closely related to F. armeniacum. F. chaquense in culture can produce the trichothecenes T-2 and HT-2 toxin, neosolaniol, diacetoxyscirpenol, and monoacetoxyscirpenol, as well as beauvericin and the pigment aurofusarin. Genome sequence analysis also revealed the presence of three previously described loci required for trichothecene biosynthesis. This research represents the first study of Fusarium in a natural ecosystem in Argentina.